Megamart Seasonal Demand Planning. Issue 1 (1st November 2018) - Thomas, Rodney
Abstract : The Megamart case study addresses demand planning challenges that retailers often face in categories that have bulky, seasonal, imported products. Historical point-of-sale data on gas grill SKUs is provided for analysis and developing appropriate product flow plan that meets the needs of all retail supply chain stakeholders.